2012
DOI: 10.1073/pnas.1206506109
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic zinc finger repressors reduce mutant huntingtin expression in the brain of R6/2 mice

Abstract: Huntington's disease (HD) is a dominantly inherited neurodegenerative disorder caused by expanded CAG repeats in the huntingtin (HTT) gene. Although several palliative treatments are available, there is currently no cure and patients generally die 10-15 y after diagnosis. Several promising approaches for HD therapy are currently in development, including RNAi and antisense analogs. We developed a complementary strategy to test repression of mutant HTT with zinc finger proteins (ZFPs) in an HD model. We tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 54 publications
4
142
0
Order By: Relevance
“…Furthermore, ZFN-based strategies have also reached the clinical phase for the treatment of glioblastoma targeting the glucocorticoid receptor gene as part of a T cell-based cancer immunotherapy (ClinicalTrial.gov Identifier: NCT01082926). In the specific case of HD, it has recently been demonstrated that zinc finger proteins (ZFP) are able to silence effectively muHTT, without affecting the expression of wtHTT, in vitro and in the R6/2 mouse brain (approximately 40% reduction in muHTT) [116]. In this study, ZFP repressors were delivered intraparenchymally using an AAV delivery system, resulting in significant improvements in HD-related neuropathology and motor deficits [116].…”
Section: Genome-editing Approaches For Hd Therapeuticsmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, ZFN-based strategies have also reached the clinical phase for the treatment of glioblastoma targeting the glucocorticoid receptor gene as part of a T cell-based cancer immunotherapy (ClinicalTrial.gov Identifier: NCT01082926). In the specific case of HD, it has recently been demonstrated that zinc finger proteins (ZFP) are able to silence effectively muHTT, without affecting the expression of wtHTT, in vitro and in the R6/2 mouse brain (approximately 40% reduction in muHTT) [116]. In this study, ZFP repressors were delivered intraparenchymally using an AAV delivery system, resulting in significant improvements in HD-related neuropathology and motor deficits [116].…”
Section: Genome-editing Approaches For Hd Therapeuticsmentioning
confidence: 98%
“…In the specific case of HD, it has recently been demonstrated that zinc finger proteins (ZFP) are able to silence effectively muHTT, without affecting the expression of wtHTT, in vitro and in the R6/2 mouse brain (approximately 40% reduction in muHTT) [116]. In this study, ZFP repressors were delivered intraparenchymally using an AAV delivery system, resulting in significant improvements in HD-related neuropathology and motor deficits [116]. Although these technologies are still in their infancy, they hold great promise not only for HD, but also other monogenic disorders.…”
Section: Genome-editing Approaches For Hd Therapeuticsmentioning
confidence: 99%
“…The precise genetic repression of detrimental genes may be a useful strategy to mitigate pathology, such as repressing the huntingtin GUIDE-seq Digenome-seq (Kim et al 2015) BLESS (Ran et al 2015) DNase-seq/ATAC-seq gene for Huntington's disease (Garriga-Canut et al 2012). Similarly, targeted activation of aberrantly silenced endogenous loci may provide therapeutic benefits (Lara et al 2012).…”
Section: Genome Engineering To Model Disease and Develop Therapeuticsmentioning
confidence: 99%
“…23 Long ZFPs have been prepared to bind CAG repeats in a selective way and to be expressed in an HD cell-line Burgunder model, with the effect of a decreased expression of the longer allele, and this was also achieved after striatal delivery using an adenoassociated virus system. 24 There are major hurdles in the path toward HTT gene silencing in humans; they include finding the appropriate delivery process, choice of target and tissue volume to be included, and timing of treatment along the course of evolution. Modes of application may include stereotactic intrastriatal delivery in the form of injections or infusions, which can be combined with convection-enhancing processes or with carriers facilitating diffusion, intraventricular injections or continuous delivery with pumps, and viral vectors or other cargo systems with selective brain targeting.…”
Section: Gene Therapymentioning
confidence: 99%